The adsorption of copper in aqueous solution onto commercial chitosan from crabshell coated on bentonite - Nguyen Thi Van (2010)
The equilibrium isotherms and the adsorption kinetics of copper onto chitosan were investigated in this study. Chitosan, a biopolymer produced from crustacean shells, has applications in various areas, particularly in drinking water and wastewater treatment due to its ability to remove metallic ions from solutions. The adsorption of Cu2+ ions from aqueous solution by non-crosslinked chitosan-coated bentonite (CCb) beads was investigated in a batch system, including the effects of pH of solution (1,2,3 and 4), initial Cu2+ ion concentration (100, 500, 1000 and 2000) and crosslinking at various contact times (30, 60, 120, 240, 360 and 720 minutes). Experimental results indicated that crosslinked CCB beads showed higher adsorption capacity compared with non-crosslinked CCB beads in the entire ranges studied. The initial Cu2+ solution concentration and the solution pH affected the adsorption capacity, i.e., increased initial Cu2+ concentration and pH resulted to increased adsorption capacity. Equilibrium adsorption data correlated well with Langmuir isotherm model. The kinetic experimental data followed pseudo-second order reaction which indicated that the chemical sorption was the rate-limiting step. The Cu2+ ions were desorbed from crosslinked CCB beads by dilute HCI acid (pH 1), with suggested that crosslinked CCB beads can be regenerated and reused to adsorb metal ions.